The concept, correlates and consequences of unmet need for contraception in Zambia - Imasuku, Eunice Ntwala Samwinga (My University, 2015)
Though the 21st century saw a rise in contraceptive use, a high proportion of women aged 15-49 (reproductive age) in developing countries are reported to have unmet need for contraception (unmet need). These women would like to stop childbearing or postpone their next birth for at least two years but are not using any contraceptives. About 200 million women of childbearing age (17%) in developing countries are estimated to have an unmet need. The 2007 Zambia Demographic and Health Survey (ZDHS) estimated Zambia’s level at 27%. Despite the concept undergoing some considerable revision, research has continued emphasizing on currently married women’s unmet need largely ignoring unmarried women, men and adolescents. This poses a challenge in that some sections of the population (unmarried women, men and adolescents) are left out. This implies that their needs are not being attended to which can result in negative reproductive health outcomes. Traditionally it is expected that married people are the ones who are sexually active but, reality has revealed that the unmarried (both adults and young people) are also sexually active with the attendant consequences. Teenage pregnancy is one of the major problems today’s world is experiencing. Zambia’s situation has been described as a crisis in that more than a quarter (28%) of adolescent females aged 15-19 have either had a child or are having their first pregnancy. However, there is paucity in studies on unmet need in Zambia. Besides, the few existing studies have tended to focus at individual factors leaving out community and programme access factors. Furthermore, these studies have not included the consequences of unmet need. Therefore this study aimed at determining the levels of unmet need among adolescents and adults (males and females) in Zambia and examined its determinants and consequences. The specific objectives of the study were: (a) determine the level of unmet need among the adolescents and adults (unmarried and married) in Zambia; (b) identify individual, household, community and programme access factors underlying unmet need among the females and males; (c) examine the association between unmet need and selected reproductive health problems (termination of pregnancy, short birth interval, infant and child mortality and high parity) in Zambia; and (d) determine the potential demographic impact of satisfying unmet need in Zambia. This cross sectional study uses data from the 2007 ZDHS. This is a nationally representative sample survey covered 8,000 households where 7,146 women aged 15-49 and 6,500 men aged 15-59 were interviewed. All the women comprised the sample for this study whereas only 3,146 currently married men whose partners were also interviewed were included. Individual men and women were the unit of analysis. The outcome variable was unmet need and relevant independent variables were selected. Data were analysed at the univariate, bivariate and multivariate levels. Percentages of individuals with unmet need were calculated to determine the levels of unmet need among the adolescents and adults in Zambia. To identify factors underlying unmet need among the married and unmarried adolescents and adults in Zambia, binary, multinomial regression and multilevel logistic regression models were employed. The Pearson chi-square test of goodness of fit and logistic regressions were used to examine the association between unmet need and selected reproductive health problems in Zambia. A simple regression equation (TFR = 6.337 – 0.055 (CPR) + e) was developed and used to determine the potential demographic impact of satisfying unmet need in Zambia. Stata 12.0 and Microsoft Excel were used to manage and analyse the data. The key findings of the study are as follows. The level of total unmet need among currently married adolescent females is 22.1% (15.0% for spacing and 7.1% for limiting) whereas it is 27.7 for currently married adult females (15.2% for spacing and 12.5% for limiting). As for the unmarried females, the level for adolescents is 9.5% (4.3% for spacing and 4.2% for limiting) and that for adults is 11.1% (6.3% for spacing and 4.8% for limiting). The level for currently married adolescent males is 41.8% with all of it being for spacing whereas the level for adults is 34.9% (21.4% for spacing and 13.5% for limiting). Hence, the average total unmet need for women is 17.6% and that for men is 38.4%. The major determinants of unmet need for spacing and limiting among the adolescent females were marital status and number of living children. The most important predictors of unmet need for spacing and limiting among adult females were marital status, visiting a health facility and fertility preference. The most important determinants of unmet need for spacing among all women were number of living children, marital status, visiting a health facility and fertility preference whereas age and region of residence including the last three factors of unmet need for spacing, were the major predictors of unmet need for limiting. As for men number of living children, educational attainment, region of residence and exposure to family planning messages on media were the most important factors determining unmet need for spacing whereas it was only region of residence for unmet need for limiting. Married adolescent females had higher odds (4.8 and 5.1, respectively) of having unmet need for spacing and limiting than their unmarried counterparts. Married adult women also were more likely (70% and 130% respectively) to have unmet need for spacing and limiting compared to their unmarried counterparts. Residing in all the other regions reduced the odds of having unmet need among men and women in Zambia. Number of living children was inversely related to unmet need for spacing among men and women. There was an inverse relationship between unmet need and educational attainment. The study also established a negative association between unmet need and exposure to family planning messages on media among men. The risk of dying before age 5 was significantly higher for children whose mothers had unmet need for limiting and total unmet need than for those whose mothers had their needs met. Women with unmet need for spacing were less likely to have 5 or more children than those with met need where as those with unmet need for limiting were more likely to have 5 or more children. Findings of the study also indicate that satisfying unmet need would reduce Zambia’s TFR of 6.2 by 58.1%, 51.6% and 54.0% according to the three models used. Besides, the TFR would be 19.2%, 30% and 25% closer to replacement level fertility for developed countries. In conclusion the estimated average level of unmet need among men (38.4%) in Zambia is higher than the disseminated level for currently married women (27%) whereas that for women is lower (17.6%). A comparison of the levels reveals that levels of unmet need among adolescents (men and women) are lower than those for adults. Levels for the unmarried women are lower than those for their married counterparts. There are differences in the major predictors of unmet need among the adolescent and adult females as well as among men and women. Satisfying unmet need has a significant effect on fertility. The results suggest the need for programmes that should specifically target men as contraceptive users in addition to addressing women’s needs. There is also need for government and service providers to intensify media campaigns that have specific messages targeted at specific groups of people.
A Doctoral Thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, South Africa; in fulfilment of the requirements for the award of PhD in Demography and Population Studies February 2015